Observations of Microphysical Properties of Wintertime Low-altitude Clouds over the Southern Ocean - EUNMI AHN (Monash University, 2019)
The Southern Ocean covers 15% of the earth’s surface and has ~87% of the clouds with frequent drizzle. These clouds influence the Earth energy budget a lot but not well presented in the global climate model and other climate related systems. Employing aircraft observations, this thesis studied the cloud microphysical properties which mean the cloud droplet numbers and their sizes which are used as input data to the climate models. The observations were made by 20 flights for 3 years (2013-2015) over the ocean of Tasmania. The result are also compared to the atmospheric satellite observations to evaluate their reliability.